Cadangan kerja-kerja peningkatan/ menaiktaraf pelabuhan perikanan LKIM Kuala Kedah, Kedah Darulaman / Mohamad Zain Hashim and Uda Saad - Hashim, Mohamad Zain; Saad, Uda (Unit Penerbitan FKAPP, 2022)
INTRODUCTION The upgrade work was done on the need for this jetty which has been damaged and eroded due to the effects of sea water and the effects of tremors and shocks by the landing of fishing boats. This work is regulated by the Kota Setar District PWD which needs to be completed within 96 weeks. The scope of work involved is as follows; Site clearing works, Jetty repair works, Demolished works, Architectural works, Civil and structure works.